2014
DOI: 10.1073/pnas.1402809111
|View full text |Cite
|
Sign up to set email alerts
|

Structure of β-galactosidase at 3.2-Å resolution obtained by cryo-electron microscopy

Abstract: We report the solution structure of Escherichia coli β-galactosidase (∼465 kDa), solved at ∼3.2-Å resolution by using single-particle cryo-electron microscopy (cryo-EM). Densities for most side chains, including those of residues in the active site, and a catalytic Mg 2+ ion can be discerned in the map obtained by cryo-EM. The atomic model derived from our cryo-EM analysis closely matches the 1.7-Å crystal structure with a global rmsd of ∼0.66 Å. There are significant local differences throughout the protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
185
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(198 citation statements)
references
References 47 publications
12
185
0
1
Order By: Relevance
“…With these improvements allowing higher resolution structures to be obtained, there have already been a number of structures published in complex with ligands and inhibitors (Fig. 3), from large soluble complexes such as the proteasome and -galactosidase to smaller membrane proteins including TRP channels and gamma secretase (Bartesaghi et al, 2014;Bai et al, 2015;Paulsen et al, 2015;Gao et al, 2016;Li et al, 2016).…”
Section: Advantages Of Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…With these improvements allowing higher resolution structures to be obtained, there have already been a number of structures published in complex with ligands and inhibitors (Fig. 3), from large soluble complexes such as the proteasome and -galactosidase to smaller membrane proteins including TRP channels and gamma secretase (Bartesaghi et al, 2014;Bai et al, 2015;Paulsen et al, 2015;Gao et al, 2016;Li et al, 2016).…”
Section: Advantages Of Electron Microscopymentioning
confidence: 99%
“…Radiation damage can also have a more subtle effect aside from the degradation of resolution, where damage causes protein side chains to shift, which could lead to subtle differences in the inhibitor binding position. Previous studies have shown that negative side chains appear to suffer radiation damage preferentially (Allegretti et al, 2014;Bartesaghi et al, 2014;Grant & Grigorieff, 2015), so if there are key negatively charged residues in the binding pocket then this may induce a significant movement of the inhibitor or show a binding mode which is not physiologically relevant. However, it should be noted that weak density for negative side chains can also be a feature of the electric potential map generated in the electron-microscopy experiment (Wang & Moore, 2017) and is not in all cases radiation damage.…”
Section: Challenges Faced By Electron Microscopymentioning
confidence: 99%
“…single-particle cryo-electron microscopy (EM) has been applied to achieve near atomic resolution of purified protein complexes 2,7,[14][15][16] , and cryo-electron tomography allows for 3D imaging of pleomorphic samples such as viral infection mechanisms of cells with resolutions on the order of a few nanometers [17][18][19] . These advances are not limited to electron tomography.…”
mentioning
confidence: 99%
“…Many software packages have been developed for single particle reconstruction, including Spider (Shaikh, Gao et al 2008, Baniulis, Yamashita et al 2009), IMAGIC (Forster and Hegerl 2007), Xmipp (Sorzano, Marabini et al 2004), BSoft Belnap 2007, Heymann, Cardone et al 2008), SPARX (Hohn, Tang et al 2007) EMAN (Heymann and Belnap 2007), EMAN2 (Tang, Peng et al 2007), Relion (Scheres 2012 Furthermore state-of-the-art direct electron detectors greatly reduce the impacts of sample charging and drift on the captured image, increasingly making atomic resolution structure determination by single particle analysis (Allegretti, Mills et al 2014) a reality not only for viruses and macromolecular assemblies but also for membrane proteins in the 500kDa range (Li, Mooney et al 2013, Liao, Cao et al 2013, Lyumkis, Julien et al 2013, Bartesaghi, Matthies et al 2014, Lu, Bai et al 2014, Campbell, Veesler et al 2015 and below.…”
Section: Figure 118 Electron Image Formation Through Em and Single Pmentioning
confidence: 99%
“…Dynamo (CastanoDiez, Kudryashev et al 2012), PyTom (Hrabe, Chen et al 2012). Furthermore state-of-the-art direct electron detectors greatly reduce the impacts of sample charging and drift on the captured image, increasingly making atomic resolution structure determination by single particle analysis (Allegretti, Mills et al 2014) a reality not only for viruses and macromolecular assemblies but also for membrane proteins smaller than 500kDa (Li, Mooney et al 2013, Liao, Cao et al 2013, Lyumkis, Julien et al 2013, Bartesaghi, Matthies et al 2014, Lu, Bai et al 2014, Campbell, Veesler et al 2015.…”
Section: Introductionmentioning
confidence: 99%